Isolation of single cells from individual mouse ovaries for flow cytometry and functional analysis - Enitome E. Bafor; Toni Martin; Jeffrey Carrell; Megan Karwan; Adrienne E. Kimmel; Uyi.G. Omogiade; Michael Sanford; Howard A. Young; Julio C. Valencia (STAR Protocols, 2023)
Summary: Here, we present a validated workflow to isolate sufficient viable single ovary cells from a single mouse without the need to pool from several mice. We provide steps essential for estrous staging, ovary harvesting and dissociation, ovary cell staining, data collection, and analysis. Our approach allows the use of these single-cell suspensions for flow sorting, flow cytometry analysis, or functional in vitro assays. Importantly, our protocol is designed to maximize the isolation of immune cells, including T cell subsets. : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.